Photosynthetic acclimation of Chlorella saccharophila to heat stress. Issue 2 (April 2017) - Patil, Smita; Pandit, Reena; Lali, Arvind
SUMMARY: Photosynthesis is one of the most important metabolic processes of algae; which is altered as a stress response. During mass cultivation of algae, temperature rise and high light are major factors that affect biomass productivity. High temperature affects photosystem II (PSII) complex irreversibly, damaging intermolecular interactions in it. However, the impact of high temperature on photosynthesis is highly variable among different algal species, depending on the prior acclimation to environmental conditions they were exposed to. The acclimation plays an important role in combating high temperature stress via regulation of photosynthetic responses. Chlorophyll a fluorescence is a highly sensitive, non‐destructive and reliable tool for such measurements of photosynthetic parameters, which provides information about algal photosynthetic performance under given conditions. To understand the effect of heat stress on the responses of high light acclimated alga Chlorella saccharophila, chlorophyll a fluorescence transients were measured after heat exposure at 40°C. Our study demonstrates that rise in temperature for short duration; during open field cultivation reversibly affects the efficiency of PSII in light acclimated alga C. saccharophila . The effects of heat stress on chlorophyll a fluorescence in this alga, grown under high light (max‐1600 μmol photons m −2 s −1 ) are presented here; they are used to infer changes in photosynthetic process during its exposure to heat, as well as their recovery after 72 h. We speculate that heat resistance may have been acquired due to prior exposures to high light.